Ideal positioning of the lower lateral cartilages associated with the optimization of the external nasal valve - Eduardo Nascimento Silva; Therency Kamila dos Santos; Lydia Masako Ferreira (Revista Brasileira de Cirurgia Plástica, 2022)
Introduction: The Lower Lateral Cartilages (LLC) positioning is directly related to good nasal functionality. When these cartilages have cephalic malpositioning, the lateral wall of the external nasal valve is not adequately supported, which can lead to valvular insufficiency. The objective is to define the ideal anatomical positioning of the LLC associated with optimizing the external nasal valve. Methods: Review narrative literature in the following databases: SciELO, LILACS and Medline. The descriptors used were: “nasal cartilages,”; “nasal obstruction,” and “rhinoplasty,” being selected 15 essential articles for the understanding of the subject. Literature review: Positioning the lateral crura of the LLC forms the contour of the nasal tip and provides stability to the lateral wall of the external nasal valve. Constantian defined the ideal positioning of the lateral crura of the LLC at the margin of the nasal alae should be 45° or less. For Toriumi, the angle is measured from the lateral crura of the LLC concerning the midsagittal plane, and the appropriate value is approximately 45°. For Silva, the positioning of the LLC is measured by the angle of divergence between the LLCs, and its appropriate value is approximately 90°. Conclusion: The external nasal valve works better when the LLCs are well-positioned, namely: the angle formed between the lateral edge of the LLCs and the alar margin is close to 45° or less; the angle formed between the LLC and the midsagittal plane is close to 45°; the divergence angle formed between the LLC is close to 90°.